Late Spontaneous Dislocation of an Ab Interno Gelatin Microstent. Issue 4 (April 2018) - Boese, Erin A.; Shah, Manjool
Abstract : Purpose: To report a case of spontaneous dislocation of a gelatin microstent 6 months after the initial uncomplicated surgery. Patients and Methods: We describe a 73-year-old man with a history of advanced primary open-angle glaucoma who had previously undergone an unsuccessful micropulse transcleral cyclophotocoagulation of the left eye. He underwent an uncomplicated combined phacoemulsification with an ab interno gelatin microstent, but was noted to have a spontaneous dislocation of the microstent 6 months postoperatively. Results: His postoperative course was largely unremarkable. He underwent a total of 5 bleb needlings, 1 immediately postoperatively because of intra-Tenon's positioning of the microstent. At his 6-month follow-up, he had a needling with both 5-flurouracil and subconjunctival bevacizumab. Despite postprocedural gonioscopy confirmation of the microstent positioning, the patient returned 1 week later with a fully dislocated microstent. The dislocation was asymptomatic, and his intraocular pressure remained in the single digits. Conclusions: The ab interno gelatin microstent is a promising new procedure, but presents unique challenges. As the procedure is still new, more complications are expected to come to light. Although gelatin microstent migration and dislocation appears to be rare, it is important to recognize this postoperative complication. To our knowledge, this is the first report of a spontaneous dislocation of the gelatin microstent without a clear inciting event. This case reiterates the importance of continued follow-up of these cases, and will hopefully help begin to shed light on preoperative considerations and patient selection.